ChemInform Abstract: Bismuth Flux Growth of CeRh6Ge4 and CeRh2Ge2 Single Crystals. Issue 12 (14th March 2013) - Vosswinkel, Daniel; Niehaus, Oliver; Rodewald, Ute Ch.; Poettgen, Rainer
Abstract Single crystals of the title compounds are grown from the elements in a bismuth flux (evacuated silica tube, 1320 K, 1 h).